PENGARUHiSTRES KERJAiDAN KEPUASAN KERJA TERHADAP.TURNOVER INTENTION KARYAWAN PADA. PT CAHAYA INDO MANDIRI - Fen Riki; Syaifullah Syaifullah (Universitas Muhammadiyah Pringsewu, 2020)
ABSTRACT In this era of increasingly fierce business competition, the success of every company is inseparable from the human resource factor. Human resources are important for the company, without people who may be companies that can help, so that they get profit. Human resources are assets that must be maintained by the company because human resources in a company can be a determinant of a company's survival. This study discusses work stress and job satisfaction on employee turnover intention at PT Cahaya Indo Mandiri. The sampling technique used in this study was saturated sampling, using a questionnaire distribution method with a total of 104 respondents who used all of PT Cahaya Indo Mandiri's employees as respondents. The data collected in this research uses descriptive method, data quality test, classic assumption test, influence test and hypothesis test with the help of SPSS (Product Statistics and Solution Services) version 25. Because the independent variable namely work stress has a significant and positive influence on turnover intention and job satisfaction have a significant partial positive towards turnover intention. The results of the F test show the variables of work stress and job satisfaction are positive and significant to the performance of employees at PT Cahaya Indo Mandiri, with the value of the test results f arithmetic 358,821 3.0864 f table values and with a significance value of 0,000 0.05.